2003
DOI: 10.1093/jee/96.4.1322
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transgenic Cotton Containing a cry1Ac Gene from Bacillus thuringiensis Against Helicoverpa armigera (Lepidoptera: Noctuidae) in Northern China

Abstract: NuCOTN 33B, a Bt transgenic variety of upland cotton (Gossypium hirsutum L.) expressing the insecticidal protein Cry1Ac from Bacillus thuringiensis Berliner sp. kurstaki, was evaluated for resistance to Helicoverpa armigera (Hübner) during 1998-2000 in northern China. The results indicated that there was no significant difference in egg densities between NuCOTN 33B and three nontransgenic varieties (DP5415, Zhongmian12, and Shiyuan321) during the season, although the survival of larvae on NuCOTN 33B seemed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…These factors may account for the lack of unequivocal field evidence of enhanced resistance to Bt cotton containing Cry1Ac in the People's Republic of China. However, it must be noted that the efficacy of Bt cotton against the cotton bollworm decreases with plant aging and thus there are some survivors in B. thuringiensis fields in the late season (31). This lower efficacy of Bt cotton later in the season may favor the survival of heterozygotes (rs).…”
Section: Discussionmentioning
confidence: 99%
“…These factors may account for the lack of unequivocal field evidence of enhanced resistance to Bt cotton containing Cry1Ac in the People's Republic of China. However, it must be noted that the efficacy of Bt cotton against the cotton bollworm decreases with plant aging and thus there are some survivors in B. thuringiensis fields in the late season (31). This lower efficacy of Bt cotton later in the season may favor the survival of heterozygotes (rs).…”
Section: Discussionmentioning
confidence: 99%
“…during the growing season, particularly from flowering onwards (Greenplate et al 1998). It was reported that toxins to helicoverpa armigera in leaves of a commercial Chinese cotton variety GK-12 that contains Cry1Ac were significantly decreased as the crop approached maturation (Wu et al 2003), while insecticidal protein levels in GK-19, a transgenic Bt cotton cultivar carrying a Cry1Ac/Cry1Ab fused gene, were higher during the early stages of cotton growth and significantly declined hereafter, behaving more variably than in GK-12 during the whole period of cotton growth and development (Wan et al 2005).…”
Section: Spatio-temporal Expression Of Insecticidal Genesmentioning
confidence: 99%
“…Transgenic Bt cotton that expresses the Cry1Ac toxin is highly effective against the major lepidopterous cotton insect pests [9]. Multiple field trials have proven that Bt cotton exhibits high insecticidal efficacy against larvae of tobacco budworm, cotton bollworm and other target lepidopterous pests and decreases the population densities of these target pest species in cotton fields [10][11][12]. However, the evolution of resistance or tolerance to Bt toxins by herbivorous insects is a serious threat to the efficacy of Bt-based insecticides and toxin-producing transgenic plants, which are generally pest specific and environmentally safe [13,14].…”
mentioning
confidence: 99%